Karakteristik Pertumbuhan Melada dan Lada Sambung - Anggraini, Nova; Evizal, Rusdi; Septiana, Liska Mutiara (Universitas Lampung, 2021)
Wild pepper of Piper colubrinum Link is used as rootstocks for grafted black pepper (Piper nigrum/Piper colubrinum) because its resistance to fungi that cause root rot disease. Grafted black pepper nurseries and plantations began to be developed by farmers in Lampung. This research aims to study the growth characteristics of wild pepper and grafted black pepper plants. The research was conducted in the field of wild pepper and grafted black pepper owned by farmers in Air Kubang Village, Air Naningan District, Tanggamus, Lampung, using survey method. Plant samples were determined randomly in the fields. The results showed that: (1) Wild pepper plants starts at the age of 1 year form plagiotropic branches with small diameters every 1-2 orthotropic branches, but slowly form orthotropic branches; (2) After the second pruning (of harvesting cuttings) 22% of the plants form orthotropic branches. The yield of pepper cuttings from the first to third harvests increased by 21-25% compared to the previous yield. In the third harvest, the production of cuttings reached 5066 cuttings (2 nodes) per 400 m2 land area or equivalent to 126,650 cuttings per ha of land harvested every 2 months; (3) At the age of 18 months, compared to non-grafted, grafted black pepper showed a greater greeness leaf index, larger stem diameter, larger plagiotropic branch diameter, higher number of orthotropic and plagiotropic branches, and 15.6% of grafted black pepper plants were flowering. Key words : Black pepper, cutting, flowering, growth, grafting, Piper colubrinum